Strategi Pengembangan Produk Kerupuk Opak Minang Yolanda - Fauzia Agustini; Dita Amanah; Dedy Ansari Harahap (STMIK Royal, 2021)
Abstract: This activity was carried out on SMEs producing snacks from sweet potatoes, namely opaque located in Medan under the name UD. Opak Minang Yolanda. Based on the observations, several problems were found, namely the texture is too fragile so it breaks easily, the taste has only one taste (original taste), the size is too large and the packaging is too simple. This activity is intended to assist UD. Opak Minang Yolanda in solving the main problems as described previously.The specific target in this activity is to improve product by diversifying products including texture, taste, size, packaging. The methods used in this activity are observations, interviews and seeking information from various literatures in the form of books, articles in journals, newspapers, relevant magazines and searching online. This activity also used a coaching pattern. The achievement of this study is the idea of opaque diversification for improvement in the sustainability of UD. Opak Minang Yolanda is an improvement in texture by thickening the volume of the opaque when formed, flavors made into various variants that are tailored to consumer tastes, sizes are made into two variants, namely large and small, making the packaging more attractive.Keywords: observation; opaque; snacks Abstrak: Studi ini dilakukan pada UMKM di Medan yang menghasilkan opak yaitu makanan ringan dari ubi dengan nama UD. Opak Minang Yolanda. Berdasarkan hasil observasi ditemukan beberapa permasalahan yaitu tekstur (permukaan) yang terlalu rapuh sehingga mudah pecah, hanya satu rasa yaitu original, ukuran (bentuk) yang terlalu besar dan kemasan (bungkus) yang terlalu sederhana. Kegiatan ini bertujuan untuk membimbing UD. Opak Minang Yolanda dalam menyelesaikan kesulitan utamanya seperti yang diuraikan sebelumnya. Sasaran utama kegiatan ini adalah membenahi produk dengan diversifikasi produk meliputi tekstur, cita rasa, ukuran, kemasan. Metode yang dilakukan pada kegiatan ini adalah melangsungkan pengamatan, tanya jawab, dan menggali fakta-fakta dari berbagai referensi seperti buku, artikel pada jurnal, surat kabar, majalah yang relevan dan juga pencarian informasi secara online. Selain itu dilakukan pembinaan untuk merubah kualitas produk UD. Opak Minang Yolanda. Capaian luaran kegiatan ini adalah buah pikiran melalui diversifikasi opak untuk memperbaharui dan keberlanjutan UD. Opak Minang Yolanda yaitu pada tekstur dengan cara lebih menambah volume opak ketika dibentuk, cita rasa yang lebih bervarian yang disesuaikan dengan selera konsumen, ukuran menjadi 2 (dua) varian yaitu besar dan kecil serta menciptakan kemasan menjadi lebih menarik.Kata kunci: makanan ringan; observasi; opak